Exploring Cognitive Development Through Speaking: How Do E-Portfolios Strengthen Speaking Skills? Introduction, Literature Review, Method, Result and Discussion, Conclusion - Belia Damayanti Br Sembiring; I Putu Indra Kusuma; Luh Indrayani (Universitas Pendidikan Ganesha, 2025)
This study explores the role of E-portfolios in students’ cognitive development in speaking, focusing on fluency and pronunciation. Using a qualitative phenomenological approach, the research investigates the experiences of eleventh-grade students at a senior high school in Buleleng, Bali, during the 2024/2025 academic year. Data were collected through researcher’s notes and semi-structured interviews and analyzed using thematic analysis. The findings indicate that E-portfolios significantly enhanced students’ fluency and pronunciation through repeated practice, self-assessment, and peer feedback. Compared to previous studies conducted at the university level, this research highlights that high school students require additional instructional support when using E-portfolios. The study concludes that while E-portfolios are an effective tool for improving speaking skills, integrating spontaneous speaking exercises and structured feedback mechanisms can further enhance students' oral proficiency.